Y+3=-4x(x+7)

Simple and best practice solution for Y+3=-4x(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y+3=-4x(x+7) equation:



+3=-4Y(Y+7)
We move all terms to the left:
+3-(-4Y(Y+7))=0
We calculate terms in parentheses: -(-4Y(Y+7)), so:
-4Y(Y+7)
We multiply parentheses
-4Y^2-28Y
Back to the equation:
-(-4Y^2-28Y)
We get rid of parentheses
4Y^2+28Y+3=0
a = 4; b = 28; c = +3;
Δ = b2-4ac
Δ = 282-4·4·3
Δ = 736
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{736}=\sqrt{16*46}=\sqrt{16}*\sqrt{46}=4\sqrt{46}$
$Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(28)-4\sqrt{46}}{2*4}=\frac{-28-4\sqrt{46}}{8} $
$Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(28)+4\sqrt{46}}{2*4}=\frac{-28+4\sqrt{46}}{8} $

See similar equations:

| 5/4x-2=10 | | /4x-15=21 | | q+4/3=7 | | m/8=5=14 | | p-0.02=9.8 | | 6x-24=12x+24 | | 0.002t=60 | | 5+6m=53 | | 3n=196 | | 3z/7+4=3 | | r/12=0.75 | | 4(u-64)=80 | | x/5+3.5=12 | | 18q=90 | | 62=4y-14 | | 6m=3.0 | | 42x-35=469 | | 20-(1/5)d=(3/10)d+16 | | 7(u+3)=63 | | 7-3x=2x-(5x-7) | | 2g+3g=40 | | 9x-8=8x+7 | | t/4+19=27 | | 8x−2=70 | | 7x-25-6=4 | | 30=6x=11x | | 54+37+x=180 | | 4x+5x=22 | | 3x-3+2=8 | | -13=-5f+48 | | 6.1+w/7=-5.1 | | .20f-14=1 |

Equations solver categories